Staying with the trouble: Collective forms and methods in performing arts in the 1920s and today - Schmitt, Konstanze (Peripeti, 2023)
Who owns Lauratibor? is the result of a collaboration between several long-standing protest movements in Reichenberger Kiez. The collectively driven opera project is a different form of activism; an opera created in self-defence, sprung from the ongoing struggle against evictions of residents and workers of all guilds in the surrounding neighbourhood of Reichenbergerstraße in Berlin-Kreuzberg.